Catalina Magdalena Hoopensteiner Wallendiner Hogan Logan Bogan se llamaba - Arnold, Tedd. (New York : Scholastic, 2004)
Presents the words and music--and varying forms of the name--of a classic camp song that dates at least from the 1940s.
"CartWheel Books."
Plastic movable eyes protrude through front cover.
Keywords: Children's songs -- Texts; Toy and movable books -- Specimens; Songs; Toy and movable books